2008
DOI: 10.1007/s00436-008-0926-3
|View full text |Cite
|
Sign up to set email alerts
|

Trichobilharzia spp. in natural conditions in Annecy Lake, France

Abstract: Annecy Lake is a well-known focus of human cercarial dermatitis in France. Identification of the parasites, however, was not performed in the past. Previous studies suspected two species, Trichobilharzia franki and Trichobilharzia regenti, based on the presence of parasites in mallards and/or morphological identification of snails emitting ocellate furcocercariae. Following a standardized molecular approach, we studied snails and furcocercariae and compared their haplotypes with those deposited in GenBank. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 23 publications
6
49
1
Order By: Relevance
“…Later on, R. lagotis and R. labiata were identified as the intermediate hosts in the Czech Republic (R. lagotis served for routine laboratory maintenance of the parasite for many years, but without determination of the level (in %) of its susceptibility); the role of R. peregra in T. regenti transmission was weakened. Now it is re-confirmed that R. peregra, besides R. lagotis and R. labiata, can play a role as a vector of T. regenti; this is in agreement with the results from France (Jouet et al 2008). Interestingly, in Iceland, R. peregra represents the dominant snail species and hosts several schistosomes (Skírnisson et al 2009), showing that both the schistosomes and the snails can adapt to each other under specific local conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Later on, R. lagotis and R. labiata were identified as the intermediate hosts in the Czech Republic (R. lagotis served for routine laboratory maintenance of the parasite for many years, but without determination of the level (in %) of its susceptibility); the role of R. peregra in T. regenti transmission was weakened. Now it is re-confirmed that R. peregra, besides R. lagotis and R. labiata, can play a role as a vector of T. regenti; this is in agreement with the results from France (Jouet et al 2008). Interestingly, in Iceland, R. peregra represents the dominant snail species and hosts several schistosomes (Skírnisson et al 2009), showing that both the schistosomes and the snails can adapt to each other under specific local conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Outbreaks can lead to the closing of swimming areas and consequently to major financial losses for touristic operators. Several foci of HCD are well known in Europe, for example in Germany (Selbach et al 2015), France ( Jouet et al 2008), the Netherlands (Schets et al 2008), and Poland (Zbikowska 2004). It is worth mentioning that in Belgium, to the authors' knowledge, no cases were ever recorded in scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…The rDNA of furcocercariae was amplified using the primers previously described (Mollaret et al 1997): C2¢B (forward) (5¢-GAA AAGTACTTTGRARAGAGA-3¢) and D2 (reverse) (5¢-TCC GTGTTTCAAGACGGG-3¢). For the amplification of the positive snails, a primer pair, previously described ( Jouet et al 2008), was used: DIX1(forward) (5¢-CGCGCTCTG GWCCKTCGCGGC-3¢) and DIX2 (reverse) (5¢-ATYTYG TYCGATTTGAGGTTG-3¢) to amplify the ITS-2 of Radix spp. For cercariae, initial denaturation at 94°C for 3 min was followed by 40 cycles of denaturation at 94°C for 45 s, annealing at 50°C for 45 s, and extension at 68°C for 2 min with a final elongation time of 10 min at 68°C.…”
Section: Molecular Analysis Of Cercariae and Positive Snailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larval stages of F. hepatica have been recorded in natural conditions in Lymnaea truncatula, Omphiscola glabra (Muller, 1774; Rondelaud et al 2001;Dreyfuss et al 2005) and even in unspecific Planorbis leucostoma Millet, 1813 (Dreyfuss et al 2002). Also conducted from a medical point of view was research on snails infected with avian schistosomes-an etiological factor of "swimmers' itch" in Lake Annecy (eastern France; Jouet et al 2008). Extremely interesting observations taking into account parasites as a biotic factor affecting snail populations living in Lake Combourg and Mont Saint-Michel Bay were made by Gerard (1997Gerard ( , 1998Gerard ( , 2001aGerard ( , b, 2003.…”
Section: Countries In Which Research Has Been Conducted On the Naturamentioning
confidence: 98%